The Influence of Receivables Turnover, Cash Flow, Inventory Turnover on Liquidity with Profitability as an Intervening Variable : Case Study of Food and Beverage Companies Listed on the IDX in 2019 – 2022 - Dwi Martalia; Ifanny Adnan Pratama (LPPM STIE PPI, 2024)
Introduction/Main Objectives: To determine the Effect of Receivables Turnover, Cash Flow, Inventory Turnover on Liquidity with Profitability as an Intervening Variable. Background Problems: The growth of large and medium manufacturing industries in 2017 increased by 4.74% compared to 2016 due to an increase in food industry production by 9.93%, while the beverage industry decreased by 2.77%. Novelty: Testing on the same variables by adding different intervening variables and objects. Research Methods: This research is a type of quantitative research of secondary data in the form of panel data. The sample used was 24 Food and Beverage companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2022 period, then processed with SPSS analysis tools including descriptive statistical tests, classical assumption tests, goodness of fit tests, hypothesis tests, sobel tests. Findings/Results: That Receivables Turnover, Cash Flow and inventory partially have a positive effect on liquidity, Profitability and Receivables Turnover, have a significant positive effect on liquidity, profitability can mediate receivables turnover and Cash Flow on liquidity. Conclusion: Conduct a comprehensive analysis of the company's financial performance, including profitability and liquidity ratios, before making investment decisions.